DENITRIFICATION IN AQUATIC ENVIRONMENTS: A CROSS-SYSTEM ANALYSIS - Piña-Ochoa E.; Álvarez-Cobelas M. (My University, 2006)
A meta-analysis was conducted on 136 data sets of denitrification rates (DR) recorded both during the period of highest water temperature and monthly in five types of aquatic ecosystems: oceans, coastal environments, estuaries, lakes and rivers. There was a gradual increase of DR from the ocean to rivers and lakes at both scales, with the rivers showing the highest DR variability. Denitrification peaked during summertime and showed highest seasonal variability in lakes and rivers. High concentrations of nitrate and interstitially-dissolved organic carbon as well as low oxygen concentration in the overlying water enhanced DR both during summer and at a seasonal scale whereas total phosphorus did at the seasonal scale only. There was a positive linear relationship between overlying nitrate and DR over the range of 1–970 µmol NO3 (r 2 = 0.86, P = 0.001). DR in lakes and rivers might reach values doubling those in the more denitrifying terrestrial ecosystems (e.g. agrosystems). Discrepancies in DR and its controlling factors between site-specific studies and this meta-analysis may arise from environmental variability at two, often confounded, scales of observation: the habitat and the ecosystem level. Future studies on denitrification in aquatic environments should address the topic of spatial heterogeneity more thoroughly.
Keywords: CONTROLLING FACTORS; META-ANALYSIS; SEASONALITY; SPATIAL HETEROGENEITY; TEMPORAL SCALES